Nanoparticle-mediated rhodopsin cDNA but not intron-containing DNA delivery causes transgene silencing in a rhodopsin knockout model - Zheng, Min (FASEB J, 2016)
Previously, we compared the efficacy of nanoparticle (NP)-mediated intron-containing rhodopsin (sgRho) vs. intronless cDNA in ameliorating retinal disease phenotypes in a rhodopsin knockout (RKO) mouse model of retinitis pigmentosa. We showed that NP-mediated sgRho delivery achieved long-term expression and phenotypic improvement in RKO mice, but not NP housing cDNA. However, the protein level of the NP-sgRho construct was only 5–10% of wild-type at 8 mo postinjection. To have a better understanding of the reduced levels of long-term expression of the vectors, in the present study, we evaluated the epigenetic changes of subretinal delivering NP-cDNA vs. NP-sgRho in the RKO mouse eyes. Following the administration, DNA methylation and histone status of specific regions (bacteria plasmid backbone, promoter, rhodopsin gene, and scaffold/matrix attachment region) of the vectors were evaluated at various time points. We documented that epigenetic transgene silencing occurred in vector-mediated gene transfer, which were caused by the plasmid backbone and the cDNA of the transgene, but not the intron-containing transgene. No toxicity or inflammation was found in the treated eyes. Our results suggest that cDNA of the rhodopsin transgene and bacteria backbone interfered with the host defense mechanism of DNA methylation-mediated transgene silencing through heterochromatin-associated modifications.—Zheng, M., Mitra, R. N., Filonov, N. A., Han, Z. Nanoparticle-mediated rhodopsin cDNA but not intron-containing DNA delivery causes transgene silencing in a rhodopsin knockout model.